STUDENT’S VISUAL THINKING ABILITY IN LEARNING LINEAR PROGRAMS USING GEOGEBRA ASSISTED LIVEWORKSHEETS - Faluthi, Nuning Rahmania; Baiduri, Baiduri; Ummah, Siti Khoiruli (FKIP Universitas Muhammadiyah Tangerang, 2024)
This research aims to describe students' visual thinking abilities when learning linear programming using LiveWorksheets assisted by GeoGebra for class XI students at SMA Negeri Ngoro. This research uses a quasi-experimental method with the research design used is Pre-Test Post-Test One Group Design. And the data analysis technique used is descriptive and inferential analysis. The sample for this research was 21 students of class XI IPA 3. The results of this research using descriptive analysis showed that students' visual thinking abilities increased after being taught with GeoGebra. This can be seen from the difference in the increase in pre-test and post-test scores obtained. Meanwhile, inferential analysis using the t-test also shows that there is an influence of using GeoGebra on students' visual thinking abilities. This can be seen because the Sig value obtained is 0.001 which is smaller than 0.05.